2018
DOI: 10.17265/2161-6256/2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fruit Fly Trapping System in Mango Orchards in Northern Côte d’Ivoire

Abstract: Abstract:Mango is the third largest export fruit in Côte d'Ivoire. However, its yield is limited by the damage caused by fruit flies (Diptera: Tephritidae). This study aimed at assessing the trapping system for fruit fly detection and monitoring in mango orchards in Northern Côte d'Ivoire. Four sites were selected in Northern Côte d'Ivoire in mango production area and in timber yard areas. Five trapping systems were tested: two food attractants (torula yeast, CeraTrap) and three sex attractants (methyl eugenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The very high proportions and prevalence of B. dorsalis in all the mango orchards in Togo is an evidence that this invasive species has settled in Togo and has undoubtedly constituted a threat to mango and other fruits production. (Bota et al 2018(Bota et al , 2020N'Da 2018;Zida et al 2020). The high proportion and prevalence of B. dorsalis in mango orchards do not seem to be explained solely by the effectiveness of the attractant used for this species but mainly by its very good adaptation to the agro-ecological conditions of the study area.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The very high proportions and prevalence of B. dorsalis in all the mango orchards in Togo is an evidence that this invasive species has settled in Togo and has undoubtedly constituted a threat to mango and other fruits production. (Bota et al 2018(Bota et al , 2020N'Da 2018;Zida et al 2020). The high proportion and prevalence of B. dorsalis in mango orchards do not seem to be explained solely by the effectiveness of the attractant used for this species but mainly by its very good adaptation to the agro-ecological conditions of the study area.…”
Section: Discussionmentioning
confidence: 78%
“…Those identified represent 77% Meyer 2005;De Meyer et al 2013). The flies identified up to species level were those of the Dacinae subfamily reported in Togo and other countries of the afrotropical region (Amevoin 2009;Ouédraogo et al 2011;Gomina et al 2012;De Meyer et al 2013;N'Da 2018;Zida et al 2020). The relatively high species richness obtained with a single study method applied over a month is an evidence that the species found in the mango orchards (which were at fruit ripening stage) and their surrounding vegetation, a favorable abiotic (temperature, relative humidity, precipitation, etc.)…”
Section: Discussionmentioning
confidence: 83%
“…Methyl eugenol (ME, Scentry Biologicals, Inc, Billings, MT), a known attractant of adult males of B. dorsalis over long distances, was placed in a slow-releasing polymeric gel form [20,21]. No killing agent was added to the attractant in the traps because the captured fies needed to be kept alive and their survival monitored.…”
Section: Attractantmentioning
confidence: 99%
“…Globalement, ce vice maintient les rendements de mangues à des niveaux extrêmement bas, de l'ordre de 3 à 7 t ha -1 , contrairement à ceux obtenus dans des conditions optimales de culture, par exemple 10 à 15 t ha -1 pour la variété Kent; et 15 à 20 t ha -1 pour les variétés Keitt et Palmer (Coulibaly, 2021). Un outil plus fréquemment utilisé pour lutter contre les mouches des fruits dans les vergers est la technique de piégeage impliquant l'utilisation de paraphéromones (Minhibo et al, 2018). Un défi majeur, cependant, est de détecter la direction correcte des mouvements des mouches des fruits afin de positionner le piège pour en capturer des quantités massives.…”
Section: Introductionunclassified